The Role of the UMY Campus in Improving the Economic Welfare of Yogyakarta Suburban Residents - Sri Rum Giyarsih; Elisya Sarah Amelia (Geosfera Indonesia, 2023)
This research aims to determine the role of the UMY campus in improving the welfare of residents around the campus. The method used was descriptive quantitative and uses a scoring analysis model. This research used several parameters collected through structured interviews and observations. These parameters were analyzed using a scoring/weighting method to determine the socio-economic conditions and level of welfare of residents around the UMY campus. The results show that 64% of the socio-economic conditions in Tamantirto Village are classified as moderate. Likewise, the welfare condition of the population is known to be 56%, including the middle class too. Based on the research results, it can be concluded that the UMY campus has a real role in improving the socio-economic welfare of the peripheral communities around the campus.